Pagelaran Wayang Sebagai Upaya Peningkatan Menulis Cerita Melalui Metode Sugesti Imajinasi (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2022)
This study aims to determine the improvement of the results of writing stories through the method of imagination suggestion in class IXA students of SMP Negeri 27 Semarang in semester 1 and to increase students' love for writing stories through the method of imagination suggestion in class IXA students of SMP Negeri 27 Semarang. This type of research is classroom action research (CAR) which consists of pre-cycle, cycle I, and cycle II. The average pre-cycle score reached 62.93 so it was categorized as incomplete and students' completeness was only 37%. The average value of my cycle reached 76.40 so it was completed completely and students' completeness was 97%. In the second cycle, the average value of the class was 82.06% with the category of attention and students who achieved 100% completeness. In the pre-cycle students are given the freedom of the theme of the wayang story. In cycle I the story is titled Bedhah Alengka. In cycle II, the story of Anoman Duta is from the famous dhalang Ki Bayu Aji Prasetya. From the results of the non-test, it was found that most of the students were happy and enthusiastic watching the wayang kulit performance as a medium with the method of imagination suggestion. This method can also help students' difficulties in writing wayang stories.